IMPLEMENTASI METODE RAPID APPLICATION DEVELOPMENT (RAD) DALAM PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN PADA SMPN 22 PADANG - Fanesyah Musvina; Sri Rahmawati; Harkamsyah Andrianof (Lembaga Pengembangan Kinerja Dosen, 2022)
The library of SMP Negeri 22 Padang in managing library data, both member data, borrowing books, returning books to making reports, still uses paper media in recording data in the library. Rapid Application Development (RAD) this method aims to shorten the time in planning, designing, and implementing a system compared to traditional methods. The RAD method has phases viz. (1) Planning the requirements of the system, (2) design workshops, (3) implementation that involves users in designing the system. The rapid application development (RAD) method is used as a reference for developing this software and is implemented into an application program using the PHP programming language, XAMPP 3.2.1 as a MySQL- based database creation software and testing is carried out using black box techniques. The results of the development of this library information system can make it easier for library admins to ma nage library data easily, officers can carry out the process of adding borrowing and returning books in the library quickly, thus saving time in making reports.